The insect fauna of granite sand plains: a naturally rare ecosystem in New Zealand. Issue 1 (2nd January 2016) - Hoare, R. J. B.; Millar, I. R.; Richardson, S. J.
ABSTRACT: Granite sand plains constitute one of New Zealand's 72 historically rare ecosystems. They occur in the alpine zone of the South Island and are known from only four sites. Invertebrates were sampled by pitfall trapping, netting and hand searching by day in two areas: the sand plains of the Lookout Range, Nelson, on 9–17 January 2008; and Mt Titiroa, Fiordland, on 3–10 February 2009. Sampling was of a preliminary, qualitative nature, due to inconsistencies in weather, year and season between the visits to the two locations, and no rigorous comparison is presented. The results of these surveys are summarised in an annotated species list (38 species), and a selection of these is illustrated. No insect species was found at both sites, and the only shared genera ( Anabarhynchus [Diptera: Therevidae], Odontria [Coleoptera: Scarabaeidae], Lyperobius [Coleoptera: Curculionidae]) have diversified throughout the alpine zone of the South Island. Many species could not confidently be identified to species level based on current knowledge, and the samples included an undescribed genus and species of Carabidae (Coleoptera), and probable new species of Prodontria and Stethaspis (Coleoptera: Scarabaeidae), Anabarhynchus (Diptera: Therevidae) and Tortricidae (Lepidoptera). A further Lepidoptera species from the Mt Titiroa sand plains ( Hierodoris extensilis Hoare, 2012 [Xyloryctidae]) has already been described as new. Whether any of these species is strictly associated with and endemic to the sand plain ecosystem remains to be confirmed. Lepidoptera recorded on Mt Titiroa outside the sand plains are listed in an Appendix.